3(4x+6)-36=

Simple and best practice solution for 3(4x+6)-36= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4x+6)-36= equation:


Simplifying
3(4x + 6) + -36 = 0

Reorder the terms:
3(6 + 4x) + -36 = 0
(6 * 3 + 4x * 3) + -36 = 0
(18 + 12x) + -36 = 0

Reorder the terms:
18 + -36 + 12x = 0

Combine like terms: 18 + -36 = -18
-18 + 12x = 0

Solving
-18 + 12x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + 18 + 12x = 0 + 18

Combine like terms: -18 + 18 = 0
0 + 12x = 0 + 18
12x = 0 + 18

Combine like terms: 0 + 18 = 18
12x = 18

Divide each side by '12'.
x = 1.5

Simplifying
x = 1.5

See similar equations:

| -1/3+4/5u=-3/2 | | z^2=5 | | 13(t-1)=8t-(8-5t) | | 1/3(5y-2)+1/6(8y+6) | | z^2-5=0 | | 4/7x+5/9 | | 8x+3/4=9x-9/4 | | (x+19)+(3x-22)+x=572 | | n+4=3n+22 | | (x+19)+(22-3x)+x=572 | | 0.80x+0.50(100)=0.40(65) | | 8^5+16w^3/4w | | 5n-17=11+3n | | (x+19)+(22-3x)=x | | 2x+3(2x-7)=-14 | | 2x+3(2x)-7=-14 | | (x+19)+(22-4x)+x=572 | | .8(.1x+.5)=-.8 | | -5x+6=-2(4y+3) | | p=(2*23)+(2*45) | | -1/2x-5y=6 | | -2[(-3-2)-2(-2+m)]=-3m-16-2 | | -2x/3-2=-7 | | 68x=95.2 | | (x+400000)+x=600000000 | | 9(x-5)-2=-47 | | (9/4)x+1 | | -x=56 | | x+(x+32)+(2x-33)=751 | | 9(t-5)+5t=7(2t+4)-12 | | (x+1)(x+4)=40 | | (x+16)+x=364 |

Equations solver categories